Analisis Two-Level Games Theory: Respons Indonesia terhadap Konflik Dagang Crude Palm Oil dengan Uni Eropa - Insan, Magfira; Pradana, Hafid Adim; Prinanda, Devita (Universitas Medan Area, 2025)
The trade conflict between Indonesia and the European Union over CPO arose due to the RED II and EUDR policies, which were deemed discriminatory and potentially harmful to various parties, particularly domestic parties. This study aims to analyze Indonesia's strategy in responding to the conflict by applying Robert D. Putnam's Two-Level Games theory. The research method used is descriptive qualitative with data collection techniques through literature review by examining various written sources that will be validated. The study results show that Indonesia has implemented strategies simultaneously at Level I through international diplomacy and at Level II through the unification of domestic actors and interests. The results indicate that among all the strategies implemented, filing a complaint with the WTO proved to be the most effective step, resulting in a victory for Indonesia. The conclusion of the research indicates that Indonesia's success is not only determined by strategies in the international arena but also by domestic pressure and support. Theoretically, this finding reinforces the understanding of how domestic factors influence foreign policy, while practically, the research suggests that the government should strengthen domestic partnerships and promote joint diplomacy with other countries in facing global trade challenges.